Analysis of Erosion Level Using Map Windows Agricultural Non-point Source Pollution (MWAGNPS) on Jeneberang Sub-watershed South Sulawesi Province - Ahmad Rifqi Asrib; M. Yanuar J. Purwanto; Sukandi S; E Eriza (International Journal of Science and Engineering, 2014)
The aims of this study was to obtain information about the level of soil erosion in Jeneberang sub watershed, as well as the impact of land management and information to determine the direction of land management in the watershed. The approach model used is MWAGNPS. MWAGNPS Model is a model of cell-based rainfall events with the main components are topographic maps, land use and soil type. This model is able to determine the source of erosion and the erosion that occurs. Simulation model showed when Jeneberang watershed has 31.66 mm of rain events with 30-minute rainfall intensity (EI30) can caused erosion 44.81 tons / ha and the sedimentation rate is 2,22 tons / ha. The source of erosion in Jeneberang sub watershed from farm/moor caused erosion is 29552.14 tons / ha and a total of 4,562,625.84 tons of sediment.